Editorial - Huamán, José (2015)
Since 1942 it appeared the first issue of the Journal of Obstetrics and Gynecology under the direction of Dr. Lucas Molina, distinguished teachers, enthusiastic members of the Peruvian Society of Obstetrics and Gynecology, through the years have been succeeding in office, demonstrating its leading capacity and determined effort to maintain constant publication. Who antecediera me, Dr. Jorge Vidal Amat, kept the frequency of issues despite the conflicting and difficult socio-economic and political situations that we lived in the country. This periodicity in the issue, more than the works selected for publication, the Journal merited be included and have a code in the Inex Medicus.